RAPAKIVI GRANITES AND RELATED ROCKS OF THE SÃO LOURENÇO-CARIPUNAS INTRUSIVE SUITE (1.32 – 1.30 Ga) AT THE SÃO LOURENÇO-MACISA MINING DISTRICT, NW PART OF THE RONDÔNIA TIN PROVINCE: II – PETROGRAPHY OF THE LATE-STAGE GRANITIC FACIES AND THE ASSOCIATED TIN AND BASE METAL DEPOSITS - da SILVA, Marly Aparecida (2025)
Syenogranites with ± biotite, syenogranites with ± biotite ± topaz and syenogranites and alkali-feldspar granites porphyries with biotite are the main late granitic facies of the São Lourenço-Caripunas Intrusive Suite recognized in the São Lourenço-Macisa mining district. These rocks occur mainly in the Saubinha and Pascana stocks and have similar petrographic characteristics with other granites with ± biotite spatially associated with the tin deposits in the Rondônia Tin Province, as well as with the evolved rapakivi granites of southern Finland. Syenogranites with ± biotite ± topaz also show an affiliation with granites specialized to rare metals related to greisen-type deposits. The primary deposits of tin and base metals occur as subparallel greisen and quartz veins and veinlets systems or in stockwork in the endo-and exocontacts of these stocks. Two petrographic types of greisen and quartz vein and veinlet are recognized in the district. Cassiterite occurs mainly in the veins and veinlets of greisen and quartz with lithium mica and topaz, while sulfides (sphalerite, chalcopyrite, galena, pyrite, and arsenopyrite) in the veins and veinlets of quartz with carbonate, chlorite, and fluorite and in chloritized zones. In general, a sequence of post-magmatic hydrothermal alteration processes can be defined as follows for the district: greisenization I/silicification I → chloritization/silicification II → greisenization II/silicification III (?).